Tin(IV) Chloride Promoted Reaction of Oxiranes with Hydrogen Peroxide - Yan, Xing; Qiao, Chunhua; Guo, Zhongwu (Synlett, 2013)
A group of substituted oxiranes were readily transformed to the corresponding β-hydroxyhydroperoxides (HHP) in good yields in ethereal SnCl4–H2O2 system in which SnCl4 acts as catalyst. Alternatively, treating oxiranes with SnCl4 first, followed by addition of ethereal H2O2 solution achieved primary gem-dihydroperoxides (DHP) in moderate yields. In the case of preparing DHP, SnCl4 first promoted the rearrangement of oxiranes to aldehydes, followed by condensation with hydrogen peroxide to provide DHP as final products.
Keywords: SnCl4; oxirane; β-hydroxyhydroperoxide; gem-dihydroperoxide